Degradation of municipal wastewater using photocatalytic silica Nano particles - Rao P, Archana; ., Nirmala (International Journal of Engineering and Technology, 2018)
The main objective of this work is to degrade the wastewater by using photo catalytic nano particles. The photo catalytic nano particles works under UV light and degrade the organic compounds that are present in municipal wastewater. The commonly used photocatalytic nano particles are silicon dioxide, platinum, silver nanoparticles, zinc oxide etc. These nano particles are produced by different methods like sol-gel process, chemical vapor deposition etc. and are characterized by different characterization techniques like X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Studies (EDS), Transmission Electron Microscopy (TEM) etc. In the present study silicon dioxide (SiO2) nanoparticles were synthesized by sol gel technique and characterized using SEM and XRD. The nanoparticles synthesized were used for the treatment of municipal wastewater. The degradation of the wastewater is evaluated based on the parameters such as degradation temperature, wastewater concentration, amount of nano particle added and time of degradation. COD analysis was carried to estimate the percentage of degradation of wastewater. It has been confirmed that photocatalytic silica nano particles can be used for the degradation of municipal wastewater. It was also observed that a higher degradation percentage of was obtained by this method as compared to the activated sludge process of treatment.Â Â Â